Characterization and medicinal applications of Karakoram shilajit; angiogenesis activity, antibacterial properties and cytotoxicity - Zahida Yaqoob; Syeda Ammara Batool; Ahmad Khan; Rabia Hussain; Mohsin Ali Raza; Mohammed S Alqahtani; Mohamed Abbas; Hassan Ali Almubarak; Fawaz F Alqahtani; Muhammad Atiq Ur Rehman (Materials Research Express, 2023)
Shilajit is a natural substance found in the Himalayan region from Nepal to Pakistan. It is a decomposition product of Royle’s spurge , white clover , and different species of molds. The decomposition takes place over a time span of centuries by the action of microorganism. In the present study, shilajit samples from four different origins including siachen khaplu shilajit (SKS), kharmang pari saspolo shilajit (KPSS), kharmang ghandus shilajit (KGS), and kharmang shilajit center (KSC) of district Skardu, Pakistan were investigated. These samples were characterized using scanning electron microscopy (SEM), Energy-dispersive x-ray spectroscopy (EDS), x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and UV-visible spectroscopy (UV/vis). SEM revealed a notable difference in the shape and size of collected samples. All samples were found to possess crystalline nature, which is confirmed from XRD. The presence of multi-components and complex silicates confirmed the presence of humic substances (HS) in shilajit. A slight disparity in physiological properties of four samples were revealed due to geographical variations and ecological conditions, which determine the natural synthesis of shilajit. All samples exhibited antibacterial effects against Gram negative bacteria; Escherichia coli (E.coli) . About 76%, 98%, and 100% of bacteria were killed by SKS, both KPSS and KGS, and KSC samples, respectively. The cell viability analysis revealed that the KPSS (66%) and KGS (53%) were cyto-compatible as compared to the SKS (23%) and KSC (25%) samples. The Chick Chorionic Allantoic Membrane (CAM) assay was used to observe the angiogenic potential for SKS, KSC, and KGS samples. Hence, shilajit sample could be a potential candidate for the medicinal applications and offer a new approach to biomedical applications.